2018
DOI: 10.3390/ma11071088
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Texture and Grain Size Distribution on the Tensile Behavior of α-Titanium

Abstract: This work analyzes the role of both the grain size distribution and the crystallographic texture on the tensile behavior of commercially pure titanium. Specimens with different microstructures, especially with several mean grain sizes, were specifically prepared for that purpose. It is observed that the yield stress depends on the grain size following a Hall–Petch relationship, that the stress–strain curves have a tendency to form a plateau that becomes more and more pronounced with decreasing mean grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…This preferred orientation feature is typical for HCP-Ti produced by swaging and/or drawing [41], suggesting that annealing treatment for a short time does not change the texture formed during RS. It has been revealed that texture plays an important role in the overall mechanical behavior of hexagonal close-packed (HCP) metals [42,43,44,45]. Thus the strong texture would influence the mechanical properties of RSA450 sample and play a different role compared with the ultrafine-grained structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preferred orientation feature is typical for HCP-Ti produced by swaging and/or drawing [41], suggesting that annealing treatment for a short time does not change the texture formed during RS. It has been revealed that texture plays an important role in the overall mechanical behavior of hexagonal close-packed (HCP) metals [42,43,44,45]. Thus the strong texture would influence the mechanical properties of RSA450 sample and play a different role compared with the ultrafine-grained structure.…”
Section: Resultsmentioning
confidence: 99%
“…This is why dislocation recovery after a short annealing can make the RS-processed Ti sufficiently tough, because of the remarkable decrease in dislocation density, as seen in Figure 3. It should be noted that, in contrast to the fine grain size that sharply enhances yield strength, the soft model for dislocation slip would result in a decrease of yield strength due to the relatively low critical resolved shear stress [44,47]. Therefore, there is an equilibrium of strength between the improvement from fine grain size and the drop due to the soft mode of dislocation slip.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the yield stress of BM was obviously lower than those of HD and CF materials by 30.9-42.1% approximately. The yield stress was considered to be associated with the grain size, grain boundaries, and so on [27]. Compared with the HD and CF materials, the grain size of BM was sharply large, leading to a reduction in the yield stress of BM.…”
Section: Discussionmentioning
confidence: 99%
“…Average grain size (diameter) is usually used to describe a polycrystalline medium; however, many investigations demonstrate the grain-size distribution actually has a measurable effect on most mechanical properties, such as tensile strength [1], yield stress [2], flow stress [3,4], hardness [5], etc. For example, good ductility and high strength can be achieved for fine grains with a small distribution width after recrystallization for commercial pure titanium alloy [6], while exceptionally large grains can result in unacceptably low mechanical strength for a pure niobium sample [7].…”
Section: Introductionmentioning
confidence: 99%